Cash Flow, Firm Size, and Earnings Persistence: Debt as Moderator: Arus Kas Operasional dan Ukuran Perusahaan: Implikasi untuk Keberlanjutan Laba dengan Tingkat Utang sebagai Variabel Pemoderasi. - Aminin Kun Arifah; Herman Ernandi (Universitas Muhammadiyah Sidoarjo, 2023)
This quantitative study aims to examine the impact of operating cash flow on earnings persistence, considering debt level as a moderating variable. Additionally, the study investigates the influence of firm size on earnings persistence, also with debt level as a moderating variable. The research employs Moderated Regression Analysis (MRA) using SPSS software. Classical assumption tests, including normality, multicollinearity, autocorrelation, and heteroscedasticity tests, are conducted prior to MRA. The findings align with previous research, indicating that debt level does not moderate the relationship between firm size and firm value. These results contribute to the understanding of the dynamics between operating cash flow, firm size, earnings persistence, and debt level, providing insights for financial decision-makers in managing and interpreting financial performance indicators. Highlights: This quantitative study examines the influence of operating cash flow on earnings persistence, with debt level as a moderating variable. It also investigates the impact of firm size on earnings persistence, with debt level as a moderating variable. The research utilizes Moderated Regression Analysis (MRA) and conducts classical assumption tests to validate the findings. The results reveal that debt level does not moderate the relationship between firm size and firm value, contributing to the understanding of financial dynamics in organizations. Keywords: Operating cash flow, Earnings persistence, Debt level, Firm size, Moderating variable.